THE INFLUENCE OF TIKTOK ADS ON GENERATION Z'S INVESTMENT INTEREST IN BIBIT MUTUAL FUND PLATFORM - Ramadina, Fitri; Rosemary, Rizanna; Nurrahmi, Febri (Jurnal Komunikasi & Media Digital, 2025)
The 2022 report from the Indonesia Central Securities Depository (KSEI) indicates that although the stock price index declined, the number of capital market investors, particularly from Generation Z, experienced significant growth. This trend is driven by the development of financial technology (fintech), which facilitates easier access to investments for younger generations. One prominent fintech platform is Bibit, which became the most popular mutual fund investment application in Indonesia in 2021. Generation Z, aged 19–25, is highly active on social media, including TikTok, which Bibit utilizes as a primary marketing platform. This study aims to analyze the influence of Bibit’s advertising exposure on TikTok on Generation Z’s investment interest in Banda Aceh. The AIDA (Attention, Interest, Desire, and Action) model is used as the analytical framework. This study employs an explanatory quantitative approach using a survey method, distributing online questionnaires. The research sample consists of 100 respondents selected through accidental sampling based on the Slovin formula. Data analysis is conducted using simple linear regression and t-tests. The results indicate that the t-value is greater than the t-table value (5.404 > 1.660), with a coefficient of determination of 0.230, meaning that Bibit’s advertising exposure on TikTok contributes 23% to investment interest. Thus, it can be concluded that Bibit’s advertising exposure on TikTok has a positive and significant influence on Generation Z’s investment interest in Banda Aceh.